Odpowiedzi

2010-03-07T17:04:21+01:00
2x(x-5)-3(x do kwadratu - 2do kwadratu) + (x-2)x

2x(x-5)-3(x²-2²)+(x-2)x=2x²-10x-3x²+12+x²-2x=-12x+12
2010-03-07T17:04:53+01:00
2x(x-5)-3(x² - 2²) + (x-2)x =2x² -10x -3x² + 6x² + x² -2x = 6x² - 12x

dasz naj:):):)??
2010-03-07T17:08:10+01:00
Zapisz w jak najprostszej postaci:
2x(x-5)-3(x do kwadratu - 2do kwadratu) + (x-2)x

2x(x-5)-3(x²-2²)+(x-2)x- to chyba tak miało być, czyli:

2x(x-5)-3(x²-2²)+(x-2)x = 2x² - 10x - 3x²-12 +x²-2x =
= 2x² - 3x² + x² - 10x - 12 = -10x - 12

POZDRAWIAM :)